2023
DOI: 10.3390/s23020835
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Wearable Wrist Pulse Detection System Based on Piezoelectric Sensor Array

Abstract: The human radial artery pulse carries a rich array of biomedical information. Accurate detection of pulse signal waveform and the identification of the corresponding pulse condition are helpful in understanding the health status of the human body. In the process of pulse detection, there are some problems, such as inaccurate location of radial artery key points, poor signal noise reduction effect and low accuracy of pulse recognition. In this system, the pulse signal waveform is collected by the main control c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Previous studies using piezo-based sensors have been able to reliably detect PWs in healthy volunteers [ 25 , 26 ], volunteers with arrythmias [ 23 ], and hypertensive patients [ 12 ]. In a recent study, the use of novel piezoelectric sensors resulted in a PW detection rate of 98% from the radial artery [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using piezo-based sensors have been able to reliably detect PWs in healthy volunteers [ 25 , 26 ], volunteers with arrythmias [ 23 ], and hypertensive patients [ 12 ]. In a recent study, the use of novel piezoelectric sensors resulted in a PW detection rate of 98% from the radial artery [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the correlations between non-invasive PTT and BP, PTT shows a good correlation with SBP, while correlations between MAP and DBP are inconsistent [ 18 , 23 , 34 ]. Two studies have provided evidence that piezosensor-derived PTT shows a significant correlation and accuracy with PTT obtained from PPG devices [ 9 , 26 ]. One study demonstrated a significant correlation between PTT and SBP during the administration of vasoactive medications in an experimental setting, which is highly relevant for the perioperative environment, as vasoactive medications are often administered to stabilize hemodynamic status [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that there is a connection between piezoelectric artery pulse waves on the nanoscale and blood pressure waves, and that this connection extends all the way up to the macroscopic thickness of the piezoelectric functional layer. As a result of the posture-specific nature of the obtained raw arterial pulse waves, it is possible to decrease motion artifacts by employing arterial pulse piezoelectric responses; hence, this technology is suitable for use in wearable continuous blood pressure monitoring [74]. Furthermore, our findings suggest that this can only be accomplished using a single-piezoelectricsensor wireless monitoring system, which is more portable than systems that need several sensors to measure pulse wave velocity.…”
Section: Piezoelectric Arterial Pulse Sensormentioning
confidence: 90%
“…However, the turning point of the dicrotic wave is not necessarily obvious. The location of the dicrotic wave is affected by many physiological factors and causes the dicrotic wave to be inconspicuous [56], as shown in Figure 3b. In contrast, Figure 3a shows the conspicuous dicrotic wave, and thus, the dicrotic notch and the diastolic peak can be obtained easily.…”
Section: Dicrotic Notch and Diastolic Peakmentioning
confidence: 99%